Analysis development of low THD single phase 11-level multilevel inverter - Nurhayati Binti Silahhuddin (School of Electrical System Engineering, 2016)
The scope of this project includes the simulation and hardware prototyping and testing of a 11-level voltage-source inverter. The simulation model of a 11-level cascaded H-bridge multilevel inverter will be modeled using PSIM software. Four different switching angle arrangment techniques will be evaluated using the modeled circuit. A hardware prototype of a 11-level cascaded H-bridge multilevel inverter using power MOSFETS as power switches will be designed and constructed. The harmonic contents of the output voltage of the constructed 11-level cascaded H-bridge multilevel inverter which are controlled using the four switching angles arrangement techniques will be evaluated experimentally and a comparison will be made.